Hacking Threat in Arab Cyberspace: Appraisal Analysis on Al-Hakirz Al-Muslimun’s Hacktivism Narratives - Reflinaldi, Reflinaldi; Rahmi, Awliya; Rezi, Melisa; Syahidin, Amal (Journal of Languages and Language Teaching, 2024)
This research aims to describe the negotiation of the attitude of the hacker group الهاكرز المسلمون (al-hākirz al-muslimūn) 'Muslim hackers' (MH) in the narrative of their hacking threats to the governments of Sweden, Australia and Israel. A descriptive-explanatory design was applied by taking three hacking threat videos on the YouTube channel "Hacker News" as a data source. Data collection was carried out through the stages of transcription, re-reading, printing, and classification. Meanwhile, data analysis referring to the appraisal theoretical framework is carried out through the stages of reduction, presentation, analysis and interpretation, and concluding. The research results showed that affect was found in 11 data (25.0%), judgment in 17 data (38.6%), appreciation in 16 data (36.4%) The type attitude is dominated by judgment and appreciation with negative intentions. This negative attitude is amplified by a force strategy that contains 'volume up' graduations to the highest level. MH stated its position firmly and strongly by making subjectivity the sole source. The research results reveal new findings amidst various previous studies which does not explain the speaker's attitude in the threat narrative they provide. As the phenomenon of cyber warfare develops, the threat of MH hacking have a significant impact in exerting political pressure on the object of the threat.